Pengaruh Kualitas Pelayanan dan Harga terhadap Keputusan Konsumen pada Axel Barbershop - Nyayu Fadilah Fabiany; Erny Melina (Universitas Batanghari Jambi, 2022)
This research was conducted using quantitative data analysis techniques. The number of samples in this study was 100 consumers of Axel Barbershop who were taken by purposive sampling. Data collection in this study was carried out using a questionnaire, and data processing was carried out using SPSS V 20 software. This can be seen from the results of the t-test and f-test scores. The results of the t-test values in this study are service quality (2.274), price (7.373), both of which t-count results are greater than the t-table value (1.660). For the results of the f-test value in this study, namely (86.849), which result is greater than the f-table value (3.09). The coefficient of determination (R2) in this study has a value of 0.633, which means that service quality and price have an influence of 63.3% on consumer decisions, and the remaining 36.7% is influenced by other variables not examined in this study.